2020
DOI: 10.36017/jahc2007-002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotherapy aquatic physiotherapy and the application of bad ragaz ring method

Abstract: This paper reviews the use of water-based therapy to rehabilitate patients with deficits of functional movement or muscle control. The properties of water are described and their relevance to the application of treatment techniques to patients in a therapy pool. The physiological effects of being immersed in water are described with reference to treatment application. It is important to ensure that the contraindications and precautions are considered before a patient can enter a therapy pool. A specific approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The department of physical medicine and rehabilitation has 3 physical therapists specialized in hydrotherapy under different modalities, and a pool equipped to perform this type of intervention. The most commonly used techniques in the institution are Bad Ragaz [ 36 ] for motor control and the Watsu technique [ 37 ] for relaxation and spasticity management. The standard physical therapy protocol and the hydrotherapy protocol were reviewed by a panel of therapists and researchers.…”
Section: Methodsmentioning
confidence: 99%
“…The department of physical medicine and rehabilitation has 3 physical therapists specialized in hydrotherapy under different modalities, and a pool equipped to perform this type of intervention. The most commonly used techniques in the institution are Bad Ragaz [ 36 ] for motor control and the Watsu technique [ 37 ] for relaxation and spasticity management. The standard physical therapy protocol and the hydrotherapy protocol were reviewed by a panel of therapists and researchers.…”
Section: Methodsmentioning
confidence: 99%
“…The nerve that works is the Autonomic Nervous System (ANS) which is allegedly the primary regulator of the heart's work activity, including heart rate and arterial pressure. Furthermore, when blood vessels undergo vasodilation, blood flow throughout the body becomes smooth (Ainslie, 2020;Juarez, 2020) and balancing the bioregulator function of the body which has an impact on reducing systole and diastole blood pressure (Júnior et al, 2020;Kumar et al, 2021;Linhares et al, 2020;Valado et al, 2022). Thus, hydrotherapy foot baths can be used as a companion treatment in lowering blood pressure in people with hypertension, especially in Dauhwaru Village, Jembrana.…”
Section: Efficacy Of Hydrotherapy Soak Feet In Lowering Blood Pressur...mentioning
confidence: 99%
“…The extremities are used as levers to activate the trunk muscles. [15,16] However, to date, no studies have reported the effects of BRRM on KOA, though it showed improved pain, [15,16] physical function, strength, and quality of life [17–20] after aquatic exercise treatment.…”
Section: Introductionmentioning
confidence: 99%